Dinamika P Tersedia, pH, C-Organik dan Serapan P Nilam (Pogostemon cablin Benth.) pada Berbagai Aras Bahan Organik dan Fosfat di Ultisols - Any Kusumastuti (Politeknik Negeri Lampung., 2014)
The experiment was conducted at field experiment of Lampung State Polytechnic from June up to November 2012, using complete randomized block design with factorial pattern, which consists of two factors, and three replications. The first factor is organic matter (POME) dosage, consists of three dosages (without POME, 25% POME with 75% soil, and 50% POME with 50% soil). The second factor is dosage of SP-36 Fertilizer (without SP-36, 1.8 g, 3.6 g, and 5.4 g SP-36 per polybag (plant) respectively. The study aims was to determine (1) The dynamics of soil available P, (2) The effect of the best POME dosage for pH, C-organic and P uptake, (3) The effect of the best SP-36 dosage for pH, C-organic and P uptake, (4) The interaction between dosages of POME and SP-36 on pH, C-organic and P uptake of plant. The observation consists of (a) Soil available P, (b) pH and C-organic (c) and P uptake of plant. The data was analysis with variance analysis, furthermore, if the result is significance, was continued with LSD test, but soil available P dynamics was presented in graphic form. The result showed that (a) Applications of POME and SP-36 increase the soil available P, (b) The media with 25% POME and 50% POME were gave the better result on pH, C-organic and P uptake by plant, (c) SP-36 fertilizer fertilizer at various doses has not been any impact on soil pH, organic-C and P uptake of plants (d) There is no interaction between POME and SP-36 fertilizer on soil pH, organic C and P uptake of plants Keywords : P Dynamics, P Uptake of Patchouli, Pogostemon cablin, ultisols